Nursing assistance in preventing childhood obesity (Research, Society and Development, 2025)
Childhood obesity is characterized as a multifactorial condition that interferes with growth and development, being associated with physical and psychological comorbidities that affect quality of life. Objective: To analyze in the literature the role of nursing in the prevention of childhood obesity. Methodology: This is an integrative literature review, with a qualitative approach and exploratory nature. The databases used were the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), PubMed, and other scientific journals, covering the period from 2020 to 2025. Results: 28 publications met the inclusion criteria, addressing nursing interventions in health education, anthropometric monitoring, physical activity promotion, and school-based actions. Final considerations: Nursing care plays a central role in the prevention of childhood obesity, especially through educational practices with families, health promotion strategies, and continuous follow-up. However, professional training and the adoption of innovative methods of care are needed to reduce dropout rates and enhance clinical outcomes.